Comparative study regarding the edilitar fund in Romanian village between the interwar period and communist period - Emilian Merce; Cristian Călin Merce; Iulia Mureşan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The archaic Romanian village was and still is ontological mentioned, if not as a human place, than as a safe and beauty place. We forgot a fundamental truth, proved by time and space: "many peasants, high misery". Making such a mistake, the Romanians reached to praise and idolize the misery which the providence will remunerate. Us the Romanians we did not have the ability, and based on this not even the calling to modernize the agrarian structures. In 1901 England had only 9% of the population involved in agriculture, while we lament about the depopulation of the Romanian villages after the Second World War, when 80% of the population was living in the country side. At the beginning of the XVI century, Thomas Morus stated that England is the country "where sheep are eating the people". The depopulation of the English villages had happened in that time. That had specific consequences, but at the same time leaded England to become the most powerful industrial country. The truth is that during the communist period the Romanian villages suffered the most major modernization from their entire history. For the total number, 70% of the dwelling stock of the Romanian villages went into use during 1948-1989. Exceptions from this fact are the Swabians and Saxon Villages, part of the Hungarian Villages and some villages from Mæarginimea Sibiului, øTara Fæagæaraøsului and Bucovina de Nord.
Keywords: 330; Romanian village; dwelling stock; inter-war period; communist period